SPEECH ACT IN BARACK OBAMA’S SPEECH - Peby Utami; Ibnu Iqbal; Farhan Najmi; Emeliya Sukma Dara Damanik (JALL (Journal of Applied Linguistics and Literacy), 2022)
The purpose of this study is to analyze Barack Obama's usage of speech acts in speech "A More Perfect Union”. The method used in this research is qualitative research. The data were collected and analyzed by collecting and classifying the utterances that are relevant to Searle’s theory on speech act’s classification. Based on the findings, the researchers discover three directives, four commisives, fifteen representatives, one declarative, and five expressives in the speech. The representative is the most common and declarative is the least common.